SISTEM INFORMASI PENGOLAHAN DATA INVENTORY PADA TOKO BUKU STUDI CV. ANEKA ILMU SEMARANG - Laila, Nur; Wahyuni, - (Jurnal Teknik Elektro, 2011)
Inventory is things or working equipment that is used in business management which isconducted or operational equipment of a company. Without an inventory, a business can not beperformed. Therefore, the exsistence of inventory is very important. CV. Aneka Ilmu Semarangconducts activities in producting and selling books. In managing its data, this company still usesmanual system, so that, the information that is produced is not quick and not careful. In on effort toimprove inventory information system which is formerly conducted manually to be a computerizedinformation system, planning and system analization are needed so that it will enable the company tomake information system from being manual into computerized.In compiling the final assignment, the writer performed effort to obtain concrete data which arereliable, so the objectives of the writing of this final assignment can be a chieved and this finalassignment can show a reliable informations in this observation, the writer used some methods whichare. Interview to some related section, the interview is conducted in oral questions or written ones,observation by performing observation to study objects, and literature study by compiling data and byreading relevant books which are related to observation matters.After the whole arrangement is made, it is kni\own that with inventory information system, thesearch for stock items will be easier and faster, because every transaction (buying or selling), availablestocks will be update (noted) automatically, so that ware house employee will find that he/she cancheck available stocks move easier and faster.Keyword : Information system, of inventory, data management